2022
DOI: 10.3389/fendo.2022.1086883
|View full text |Cite
|
Sign up to set email alerts
|

Gene mutations associated with fertilization failure after in vitro fertilization/intracytoplasmic sperm injection

Abstract: Fertilization failure during assisted reproductive technologies (ART) is often unpredictable, as this failure is encountered only after in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) have been performed. The etiology of fertilization failure remains elusive. More and more mutations of genes are found to be involved in human fertilization failure in infertile patients as high throughput sequencing techniques are becoming widely applied. In this review, the mutations of nine important g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 88 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…In the present study, we found that DEGs (including ACTL7A, ACTRT3, and SPESP1 ) were significantly enriched in cell components, such as the germ cell nucleus and male germ cell nucleus. ACTL7A is essential for early embryonic development, and its reduction could lead to poor embryonic development and even infertility [ 47 , 48 , 49 , 50 ]. The deletion of SPESP1 led to an abnormal distribution of multiple proteins in mouse spermatozoa, reduced the sperm fusion capacity, and reduced the number of pups [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that DEGs (including ACTL7A, ACTRT3, and SPESP1 ) were significantly enriched in cell components, such as the germ cell nucleus and male germ cell nucleus. ACTL7A is essential for early embryonic development, and its reduction could lead to poor embryonic development and even infertility [ 47 , 48 , 49 , 50 ]. The deletion of SPESP1 led to an abnormal distribution of multiple proteins in mouse spermatozoa, reduced the sperm fusion capacity, and reduced the number of pups [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…As well as facilitating the vertical transmission of infertility-inducing mutations, ICSI may also result in the creation of de novo mutations in the offspring due to the aberrant repair of sperm DNA damage in the newly formed zygote [ 88 , 97 ]. Such de novo mutations may then result in compromised fertility in the offspring affecting oocyte maturation, embryo development and normal testicular function [ 98 , 99 , 100 , 101 ].…”
Section: Role Of the Assisted-conception Industrymentioning
confidence: 99%